Prevalence and clinical features of microfistulas between the coronary artery and left ventricle: single-center experience - Mehmet Doğan; Hamza Sunman; Ahmet Akyel; Tolga Çimen; Murat Bilgin; Tolgahan Efe; Mehmet Erat; Bahtiyar Aralov; Kadriye Gayretli Yayla; Mehmet Aytürk; Sadık Açıkel; Ekrem Yeter (KARE Publishing, 2014)
Objectives: Coronary artery fistula is an infrequent malformation, and the prevalence was reported as approximately 0.1-0.4% in previous studies. However, the number of studies about microfistulas from coronary arteries to the left ventricle is inadequate, especially in the Turkish population. The purpose of this study was to evaluate the prevalence and clinical features of microfistulas in subjects undergoing coronary angiography for the assessment of coronary artery disease. Study design: In this retrospective study, we researched the cardiac catheterization laboratory database between January 2008 and July 2013. The presence of microfistulas was established according to the following criteria: 1) direct filling of the heart cavity during selective coronary injection without interposing 'capillary' phase or venous filling, and 2) visualization of small vessels interposed between the epicardial coronary vessels and the heart cavity and emptying into the heart. Results: Microfistulas were found in 12 (0.11%) of the 11403 coronary angiographies. There were 7 (58.3%) female patients (mean age, 70.2+-10.8 years), and contemporary severe coronary artery stenosis was noted in 2 (16.7%) patients. Chest pain was the most frequently encountered complaint, followed by dyspnea. Microfistulas originated from the left anterior descending artery (100%), circumflex artery (66.7%), and right coronary artery (58.3%). In addition, multiple microfistulas were seen in 6 (50%) patients, bilateral microfistulas in 3 (25%) patients and unilateral microfistula in 3 (25%) patients, and all of them terminated in the left ventricle. Conclusion: Our study found an overall incidence of microfistulas of 0.11%. Microfistula is a rare cardiac anomaly that sometimes causes cardiac symptoms; otherwise, it is detected during routine coronary angiography.